Pengaruh Preventing Dan Ajaran Tri Pantangan Terhadap Kecenderungan Berperilaku Curang - Dewi Kusuma Wardani; Deazilva Ian Herlicia (Universitas Katolik Soegijapranata, Semarang, 2023)
The purpose of this study is to ascertain the impact of prevention and tri pantangan teachings on the tendency of dishonest behavior. Research of this kind is quantitative. By giving out surveys to students at Yogyakarta's Tamansiswa University, primary data are collected. Convenience sampling is the sample method employed, while IBM SPSS Statistics 20 is used to analyze the data. Data was gathered by sending pupils access to Google forms via the Whatsapp messaging service. One hundred surveys were processed in total. The findings of this study demonstrate that tri pantangan lessons and prevention have a major impact on the tendency of dishonest behavior, while prevention has the opposite effect. The tri pantangan's teachings have an adverse effect on the the tendency of dishonest behavior